2005
DOI: 10.1139/w04-130
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocarbon biodegradation in oxygen-limited sequential batch reactors by consortium from weathered, oil-contaminated soil

Abstract: We studied the use of sequential batch reactors under oxygen limitation to improve and maintain consortium ability to biodegrade hydrocarbons. Air-agitated tubular reactors (2.5 L) were operated for 20 sequential 21-day cycles. Maya crude oil-paraffin mixture (13,000 mg/L) was used as the sole carbon source. The reactors were inoculated with a consortium from the rhizosphere of Cyperus laxus, a native plant that grows naturally in weathered, contaminated soil. Oxygen limitation was induced in the tubular react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 21 publications
0
7
0
5
Order By: Relevance
“…The isolation of these species is not surprising due to their frequency in contaminated soils (Barathi and Vasudevan 2001;Ueno et al 2007). All of the other species found in the consortia have been shown to degrade hydrocarbons (Chaineau et al 1999;Lafortune et al 2009;Medina-Moreno et al 2005;Nikakhtari et al 2009;Owsianiak et al 2009;Rahman et al 2002).…”
Section: Resultsmentioning
confidence: 99%
“…The isolation of these species is not surprising due to their frequency in contaminated soils (Barathi and Vasudevan 2001;Ueno et al 2007). All of the other species found in the consortia have been shown to degrade hydrocarbons (Chaineau et al 1999;Lafortune et al 2009;Medina-Moreno et al 2005;Nikakhtari et al 2009;Owsianiak et al 2009;Rahman et al 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Kim and Jaffé26 reported the capacity of facultative Ralstonia picketii PKO1 to degrade toluene, whereas Juhas et al 27 showed the ability of Pseudomonas aeruginosa and Burkholderia cepacia to form mixed biofilms and hold intercellular communication. Furthermore, the strain AR‐46 of Acinetobacter haemolyticus has been reported to degrade n‐hexadecane28 and Achromobacter xylosoxidans was able to grow on crude oil under oxygen‐limiting conditions 29…”
Section: Resultsmentioning
confidence: 99%
“…However, certain microbes present within WB8 and WB13 have previously been isolated from petroleum‐related environments: Pseudomonas pseudoalcaligenes , or more generally Pseudomonas spp. (Whyte et al, 1997; Leahy and Colwell, 1990; Medina‐Moreno et al, 2005); an uncultured bacterium clone, PL‐10B5, from production waters within a low‐temperature, biodegraded oil reservoir (Grabowski et al, 2005); and Acinetobacter spp. (Leahy and Colwell, 1990; Margesin et al, 2003).…”
Section: Discussionmentioning
confidence: 99%